The Implementation of the LMKN Decree Number: 20160512rkbd/LMKN-Plenary/Tarifroyalty/2016 in Terms of Payments Managed by Cafes in Surabaya Thorugh The Karya Cipta Indonesia Foundation at the East Java Regional Representative Office - El Shaddai, Gempita Gloria Karunia; Maharani MTVM, Sri (Nusantara Science and Technology Proceedings, 2020)
This study aimed to figure out the implementation of the LMKN Decree Number: 20160512RKBD/LMKN-Plenary/TariffRoyalty/2016 in terms of payments managed by cafes in Surabaya through the Karya Cipta Indonesia Foundation at the East Java Regional Representative Office. This research used juridical empirical methods, namely law research by taking a direct approach to the reality and legal facts that exist in the community. The juridical empirical approach is carried out by observing the objects directly, then analyzing problems that occur in society to obtain the legal fact that is used to support the research and use of the law. The results of research at the Karya Cipta Indonesia Foundation for the East Java Regional Representative Office and cafes’ manager in Surabaya regarding the implementation of the LMKN Decree Number: 20160512RKBD/LMKN-Plenary/TarifRoyalti/2016 is that the payment has been made and implemented following the LMKN Decree Number: 20160512RKBD/LMKN-Plenary/TarifRoyalti/2016. However, many cafe managers do not make royalty payments and ignore the existence of the LMKN decree caused by several factors. The implementation of the LMKN decree number: 20160512RKBD/LMKN-Plenary/TarifRoyalti/2016 has met several challenges both internally and externally.